Progression from external pilot to definitive randomised controlled trial: a methodological review of progression criteria reporting - Mellor, K; Eddy, S; Peckham, N; Bond, CM; Campbell, MJ; Lancaster, GA; Thabane, L; Eldridge, SM; Dutton, SJ; Hopewell, S (BMJ Publishing Group, 2021)
Objectives Prespecified progression criteria can inform the decision to progress from an external randomised pilot trial to a definitive randomised controlled trial. We assessed the characteristics of progression criteria reported in external randomised pilot trial protocols and results publications, including whether progression criteria were specified a priori and mentioned in prepublication peer reviewer reports.